Desenvolvimento de um sistema para monitoramento remoto em centrais de microgeração fotovoltaica - Halmeman, Radames Juliano [UNESP] (2014)
To evaluate the performance of microgeneration systems is necessary to collect data about production and consumption of energy. In this work, a system was developed for monitoring the production and consumption of energy in micro generation photovoltaic station. The experiments were performed in the central distributed micro generation photovoltaic - MGD-PV in Sítio Modelo in Campus Lageado and Renewable Energy Laboratory, Department of Rural Engineering in College of Agronomic Science (FCA) UNESP / Botucatu. To data collect the system uses voltage and current sensors and devices based on free hardware for managing and transmitting data (Arduinos). Data are transmitted via wireless (ZigBee) to a central database where one computer runs programs developed to store, manage and transmit the data to the Internet. To monitor the operation and access the data was created a page on the Internet. The downloaded data can be done in CSV - Comma-Separated Values, widely used and allows the import for several software tools. The system efficiency was 96% in the amount of recorded data.